Detection and Characterization of Inclusions in Impedance Tomography (2011)
The topic of this work are two further developments of the Factorization method for electrical impedance tomography.We present a modification of this method that is capable of detecting mixed inclusions, i.e. both inclusions with a higher as well as inclusions with a lower conductivity than the background medium. In addition, we derive a new method to compute the conductivity inside inclusions after they have been localized.